2005
DOI: 10.1289/ehp.8193
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of a Fungal Volatile Compound

Abstract: Objective: 3-Methylfuran (3-MF) is a common fungal volatile product with active biologic properties, and previous studies have indicated a contribution to airway disease. The aim of the present study was to assess the acute health effects of this compound in humans.Design: Acute effects were assessed via chamber exposure to (1 mg/m3) 3-MF.Participants and measurements: Twenty-nine volunteers provided symptom reports, ocular electromyograms, measurement of eye tear film break-up time, vital staining of the eye,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…These results are supported by two experimental studies on humans that found significant objective and subjective signs of mild mucosal irritation in the eyes and airways during exposure to 3-methylfruran or 1-octen-3-ol over a period of 2 h in a closed chamber (Wålinder et al, 2005;Wålinder et al, 2008). Korpi et al (1999) found that 1-octen-3-ol is more potent than other compounds and that its effect is stronger when combined with other compounds.…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 67%
See 1 more Smart Citation
“…These results are supported by two experimental studies on humans that found significant objective and subjective signs of mild mucosal irritation in the eyes and airways during exposure to 3-methylfruran or 1-octen-3-ol over a period of 2 h in a closed chamber (Wålinder et al, 2005;Wålinder et al, 2008). Korpi et al (1999) found that 1-octen-3-ol is more potent than other compounds and that its effect is stronger when combined with other compounds.…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 67%
“…According to a more recent review of the literature, the most obvious adverse health effects of MVOC exposure are eye and upper-airway irritation (Korpi et al, 2009). The exposure levels found in the chamber studies mentioned above were 1 mg/m 3 for 3-methylfuran and 10 mg/m 3 for 1-octen-3-ol (Wålinder et al, 2005;. The recommended maximum level of 1-octen-3-ol for indoor air, based on data from animal studies, is estimated to be 100 µg/m 3 (Korpi et al, 1999).…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 99%
“…However, concentrations measured in experimental human studies are 1 and 10 mg/m 3 for 1-octen-3-ol and 3-methylfran, respectively, (Wålinder et al, 2005;Wålinder et al, 2008), while in animal studies they range from 58 to more than 10,000 mg/m 3 for 1-octen-3-ol, 3-octanol and 3-octanone (Korpi et al, 1999). These are higher than levels measured indoors.…”
Section: Introductionmentioning
confidence: 76%
“…One such example, 3-methylfuran, was reported to cause acute effects in mucous membranes in a human experimental study (Wålinder et al, 2005). Another such example, 2-ethylhexanol, is used as a solvent but is also derived from microorganisms (Nalli et al, 2006) and shares some chemosensory features with other long chain alcohols, such as 1-octanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation